Senate Sends Academy Aid Bill to Ike - Vallejo Times-Herald (Vallejo Times-Herald)
A bill increasing from $50,000 to $75,000 the maximum annual Federal grant payable to the California Maritime Academy in Valljeo and to three other state operated maritime academies was sent by the Senate to President Eisenhower yesterday for his signature.